L’altérité au prisme de la polytextualité : les artefacts science-fictionnels de Points chauds (Laurent Genefort) - Simon Bréan (ReS Futurae)
Points chauds (Hot Spots), by Laurent Genefort (2012), presents fictional testimonies in which recognition and distancing are combined to help understand, but also feel, what alien otherness would imply for human beings. Polytextuality presents itself here not only as an aesthetic choice, but above all as a modality of cognitive access to what establishes otherness, that is to say mostly the point of view adopted. In this paper, we will better understand the textual strategies employed by Laurent Genefort to engage a specific dynamic involving the understanding of alien otherness, through a polytextuality playong with scientific fiction artifacts varying in status and nature.